Cr(VI) removal from groundwater by calcium alginate coating microscale zero‐valent iron and activated carbon: Batch and column tests. Issue 32 (16th June 2022) - Duan, Yijun; Meng, Fanbin; Li, Miao; Hou, Xiaoshu; Zhang, Shuo; Li, Jiacheng; Liu, Xiang
Abstract: Although most of the studies focus on the nanoscale zero‐valent iron (nZVI), it still ineffective when comes to in situ utilization due to its intrinsic drawbacks such as rapid aggregation, biotoxicity, high cost, complex preparation process, and so forth. With advantages of lower health risk, lower cost, and simpler fabricate method, microscale zero‐valent iron (mZVI) shows more attractiveness for groundwater remediation than nZVI if its main problem, passivation, can be alleviated. In order to overcome the passivation of mZVI, (mZVI+AC)/CA was produced by encapsulating mZVI and activated carbon (AC) in spherical calcium alginate (CA) matrix in this study. The method effectively solved the passivation of mZVI and showed great long‐effective removal of Cr(VI). The Cr(VI) removal efficiency of (mZVI+AC)/CA could maintain 1.6–2.69 times as much as that of pure mZVI for 0–1500 pore volumes. The maximum Cr(VI) removal capacity reached 100.47 mg/g, which exceeded most of mZVI‐based materials and even some nZVI‐based materials. In addition, mechanism of Cr(VI) removal was revealed by X‐ray diffraction and X‐ray photo‐electron spectroscopy. The results showed that chemisorption, physisorption, reduction, oxidation, and precipitation were involved in the process. Pseudo‐second order model and Freundlich isotherm model were best fitted in kinetics and isotherm experiments, respectively. Abstract :